Research of total levels on DNA methylation in plant based on HPLC analysis - Chen, Qiang; Tao, Siyuan; Bi, Xiaohua; Xu, Xin; Wang, Lanlan; Li, Xuemei (Scientific Research Publishing, 2013)
HPLC analysis is important for determination of total level on DNA methylation in plants. It can be used to help characterise epigenetic changes during growth, development and stress. HPLC methods have been optimised for mammalian and microbial DNA, but not for plants. This article examines several important factors in the HPLC analysis of plant DNA methylation including extraction and purification of DNA and HPLC conditions choice by using leaves of rice seedling. The experimental results showed that RNA of nucleic acid was removed by using RNase A. This study also identified critical components of HPLC analysis. With the optimized method of HPLC conditions, the better result was achieved in the chromatogram of cytosine and 5-methylcytosine in genomic DNA acid hydrolysis. The study would offer a comprehensive guide for the stringent analysis of DNA methylation in plants.
Keywords: DNA Methylation; Cytosine; 5-Methylcytosine; High Performance Liquid Chromatography; Mobilephase